(untitled) - Flecky, Kathleen; Gitlow, Lynn (Sudbury, Mass., 2011)
Foundations of service-learning / Kathleen Flecky -- Occupational therapy education : preparing students for the future practice / Lynn Gitlow -- Who sits at the head of the table? A reflection on community, student, and faculty partnerships / Beth P. Velde, Doris T. Davis, Gary R. Grant -- Cross-cultural service-learning : an introduction and best practices / Joy D. Doll -- Providing voice to vulnerable populations through service-learning infused in an occupational therapy program / Ingrid M. Provident, Anne Marie Witchger Hansen, Jaime Phillip MunÌƒoz -- Service-learning, health promotion, and occupational therapy : a good fit / Callie Watson, Kristin Haas -- Occupation of learning through service engagement : an occupational therapy assistant program perspective / Diane Sauter-Davis -- Translating service-learning theory into practice in occupational therapy education / Karen Atler -- Occupational therapy service-learning and early childhood education / Roger I. Ideishi -- Community engagement : a process for curriculum integration / Kimberly Hartmann -- Involve me and I understand : differentiating service-learning and fieldwork / Patricia Crist -- Conclusions and reflections on service-learning in occupational therapy education / Lynn Gitlow, Kathleen Flecky.
Keywords: Occupational therapy -- Study and teaching; Service learning; Dịch vụ học tập; Occupational Therapy -- education; Trị liệu nghề nghiệp